اللغة مفتاح لكل تأويل - حنيشات محمد; خميس عبد العزيز (University of Eloued جامعة الوادي, 2024)
With Gadamer, interpretation experienced great development, its nature, and its function, until it became called philosophical interpretation, and he made the linguistic experience a central issue in it, describing language as an interpretable human given that makes every interpretation clear. Language, then, has become the title of every subject; Heritage and art are a language. Existence is like this, and thus language becomes an attribute of every interpretive description, through which every ambiguous thing is clarified and every alienation is dispelled. عرف التأويل مع غادامير تطورا كبيرا، ماهية، ووظيفة، حتى أصبح ينعت بالتأويل الفلسفي، وقد جعل التجربة اللغوية مسألة مركزية فيه، بوصف اللغة معطى إنساني مؤول يجلي كل تأويل. إن اللغة، إذًا باتت عنوانا لكل موضوع؛ فالتراث، والفن لغة. ويكون الوجود كذلك، وهكذا تصبح اللغة صفة لكل موصوف تأويلي، بها يوضح كل مبهم، ويبدد كل اغتراب.
التجربة اللغوية عند غادامير أنموذجا
Keywords: اللغة; التأويل; التجربة اللغوية; غادامير; language; interpretation; linguistic experience; Gadamer